Элементы теории устойчивости движения гибридных систем (обзор) - Мартынюк, А.А. (Прикладная механика, 2015)
Наведено достатнi умови рiзних типiв стiйкостi трьох класiв гiбридних систем, що моделюються динамiчними рiвняннями на часовiй шкалi, системами з пiслядiєю при iмпульсних збуреннях та рiвняннями в банаховому просторi. Окремi загальнi результати iлюструються прикладами i деякими застосуваннями з механiки i теорiї нейронних мереж. The sufficient conditions of different types of stability are given for three classes of hybrid systems, that are modeled by the dynamical equations over the time scale, the systems with aftereffect under impulsive perturbations, and the equations in the Banach space. Some general results are illustrated by examples and applications to mechanics and theory of neural networks.